2008
DOI: 10.1177/239700220802200304
|View full text |Cite
|
Sign up to set email alerts
|

Work Role Stressors and Turnover Intentions: A Study of IT Personnel in South Korea

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 62 publications
1
21
0
1
Order By: Relevance
“…The abundance of studies examining affective commitment show that, as expected, employees who have a strong emotional attachment to their organizations tend to have lower intentions to leave (e.g. Ahuja et al 2007;Baroudi 1985;Chang 2008;Igbaria and Greenhaus 1992;Igbaria and Siegel 1992;Paré and Tremblay 2007;Rigas 2009;Shahnawaz and Jafri 2009;Thatcher et al 2002-3;Thatcher et al 2006). One study examined continuance commitment and also found that it has the same effect as affective commitment.…”
Section: Desirability Of Leavingmentioning
confidence: 95%
See 1 more Smart Citation
“…The abundance of studies examining affective commitment show that, as expected, employees who have a strong emotional attachment to their organizations tend to have lower intentions to leave (e.g. Ahuja et al 2007;Baroudi 1985;Chang 2008;Igbaria and Greenhaus 1992;Igbaria and Siegel 1992;Paré and Tremblay 2007;Rigas 2009;Shahnawaz and Jafri 2009;Thatcher et al 2002-3;Thatcher et al 2006). One study examined continuance commitment and also found that it has the same effect as affective commitment.…”
Section: Desirability Of Leavingmentioning
confidence: 95%
“…For example, a study of 304 IT personnel working in the Seoul and Gyeonggi regions of South Korea indicated that work-family conflict negatively impacted organizational commitment and job satisfaction, and was positively related to turnover intentions (Chang 2008). Furthermore, in a study involving Singapore and New Zealand IT employees, it was found that employees from both countries identified work-family conflict as sources of stress and reasons for turnover (Hunter et al 2008).…”
Section: Social Factorsmentioning
confidence: 96%
“…The demands may lead to role stresses such as RO. Additionally, when unreasonable expectations are held about the quality of work, employees may feel less satisfi ed with work (Beehr et al, 1976), which in turn may lead to higher level of intention to leave (Chang, 2008). This is especially true when they are unable to fi nish the work within the designated timeframe.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers (Chang, 2008;de Ruyter, Wetzels, & Feinberg, 2001) have found a signifi cant negative relationship between modeling (SEM) was chosen for hypothesis testing instead of multiple regressions because it is a more sophisticated way of data analysis. More committed employees show greater affection to their organization, which may result in longer tenure with the organization.…”
Section: Methodsmentioning
confidence: 99%
“…Beberapa hasil penelitian menjelaskan hubungan yang signifikan antara konflik dan komitmen organisasi (Chang, 2008). Penelitian-penelitian tersebut menganalisis hubungan konflik secara umum dengan komitmen organisasi.…”
Section: Pengembangan Hipotesisunclassified